2015
DOI: 10.1038/ncomms9042
|View full text |Cite
|
Sign up to set email alerts
|

Bax monomers form dimer units in the membrane that further self-assemble into multiple oligomeric species

Abstract: Bax is a key regulator of apoptosis that mediates the release of cytochrome c to the cytosol via oligomerization in the outer mitochondrial membrane before pore formation. However, the molecular mechanism of Bax assembly and regulation by other Bcl-2 members remains obscure. Here, by analysing the stoichiometry of Bax oligomers at the single-molecule level, we find that Bax binds to the membrane in a monomeric state and then self-assembles in <1 min. Strikingly, active Bax does not exist in a unique oligomeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
186
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(198 citation statements)
references
References 60 publications
10
186
0
2
Order By: Relevance
“…Our results suggest that α9 is the trigger site of Bax/ Bak and that a stable interaction between α9 and the OMM is sufficient to initiate the series of conformational changes and homo-oligomerization. Consistent with this conclusion, a recent study with reconstituted membranes suggested that, once in the membrane, Bax molecules form dimers, which further self-assemble into homo-oligomers (Subburaj et al 2015). Furthermore, an α9-α9 interface was recently detected in the homo-oligomers of Bax and Bak (Bleicken et al 2014;Gahl et al 2014;Iyer et al 2015).…”
Section: Omm As the Direct Activator Of Bax/bak Following Neutralizatsupporting
confidence: 67%
“…Our results suggest that α9 is the trigger site of Bax/ Bak and that a stable interaction between α9 and the OMM is sufficient to initiate the series of conformational changes and homo-oligomerization. Consistent with this conclusion, a recent study with reconstituted membranes suggested that, once in the membrane, Bax molecules form dimers, which further self-assemble into homo-oligomers (Subburaj et al 2015). Furthermore, an α9-α9 interface was recently detected in the homo-oligomers of Bax and Bak (Bleicken et al 2014;Gahl et al 2014;Iyer et al 2015).…”
Section: Omm As the Direct Activator Of Bax/bak Following Neutralizatsupporting
confidence: 67%
“…Regulatory interactions between Bax and other Bcl-2 proteins can only be observed in the presence of the OMM or liposomes (17,18). Recent studies suggest that Bax is inserted in mitochondrial membranes as a monomer that oligomerizes once inserted (19)(20)(21). These studies also have shown that Bcl-x L inhibits Bax by dissociating Bax oligomers.…”
mentioning
confidence: 68%
“…The underlying mechanism is not fully understood, but it is believed that ART is responsible for maintaining the inactive monomeric form of Baxα proteins. Upon stimulation by cell death signals, Baxα monomers undergo conformational changes, form oligomers, and target mitochondria (2633). Although the exact nature of the conformational changes is controversial, it is generally accepted that the death signal-induced exposure of the BH3 domain is critical for Baxα activation.…”
Section: Introductionmentioning
confidence: 99%